Vienna blood. Season 4 [videorecording (DVD)] - Thompson, Steve (Stephen); Beard, Matthew, 1989-; Maurer, Jürgen (Actor); Finckh, Luise von, 1994-; Bullmore, Amelia, 1964-; Hill, Conleth, 1964-; McKenna, Charlene; Bargen, Raphael von, 1977-; Ellers, Josef; Kariolou, Roman, 1983-; Tallis, Frank (PBS Distribution, 2025)
Vienna, 1909: The double murder of an arms dealer in police custody and a senior public official has shaken Vienna to its core. Doctor Max Liebermann has only just returned from a lecture tour when Inspector Oskar Rheinhardt asks for help in what could be the most dangerous case of their careers. Oskar and Max uncover a conspiracy that leads to the very heart of the government. Can the crime-fighting duo do enough to stop the seditious mole known as 'Mephisto' from bringing the Austro-Hungarian Empire to destruction? And will their lives ever be the same again?